Physical Education and Anti-Blackness. Issue 9 (21st November 2020) - Culp, Brian
Abstract : This commentary is not intended to be an all-inclusive "catch-all" but a starting point to inspire behavior change, cultural fluency, and an "ideological repositioning" of how we think about our professional work. In defining anti-Blackness, the article provides perspectives from educational literature, research, and personal observations before providing a challenge to SHAPE America and all professionals involved in efforts related to the promotion of quality physical education.